Trophic transfer of toxic elements in the estuarine invertebrate and fish food web of Daliao River, Liaodong Bay, China. Issue 1 (15th December 2016) - Guo, Bobo; Jiao, Deqi; Wang, Jing; Lei, Kai; Lin, Chunye
Abstract: In order to study element accumulation and trophic transfer in the food web, sixteen benthic invertebrate species and nine fish species were collected from the Daliao River estuary for analysis of toxic elements and nitrogen stable isotope in the muscle tissue. The concentrations ranged between 1.44–17.98, 0.01–9.30, 0.17–36.15, 0.7–145.4, 0.01–0.33, 0.14–14.88, 0.10–2.51, 0.02–0.14, and 19.3–221.1 mg kg − 1 for As, Cd, Cu, Hg, Ni, Pb, Sb, and Zn, respectively. As, Cd, Cu, and Zn were significantly higher in the benthic invertebrates than in fish, whereas Hg and Sb were significantly lower. In addition, the benthic invertebrates were characterized by the highest bioaccumulation factor (BAF) for Cd, whereas the fish were characterized by the highest BAF for Hg. A significant decrease in Cd, Cr, Cu, and Ni levels, and a significant increase in Hg and Sb levels were observed with increasing trophic levels. Graphical abstract: Highlights: Toxic elements and trophic level were determined in biota from Daliao River estuary. Benthic invertebrates had higher As, Cd, Cu, Zn and lower Hg and Sb levels than fish. Benthic invertebrates accumulated high As levels, while fish accumulated high Hg levels. Cd, Cr, Cu, Ni levels decreased, and Hg and Sb levels increased with trophic levels.